Validation of Student Worksheet (LKPD) Based Argument-Driven Inquiry (ADI) Assisted with PhET to Train Argumentation Skills the Pressure Materials (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2022)
This study aims to determine the feasibility of student worksheets based on the PhET-assisted Argument-Driven Inquiry (ADI) to train students’ argumentation skills on the subject of substance pressure. This research uses Research and Development (R&D) research using a 4-D development model (Define, Design, Development, and Dissemination). This study uses the LKPD validation sheet instrument, which consists of 6 assessment aspects. The research data was obtained from the validation test results by three validators consisting of two physics education lecturers and one science education lecturer at the University of Riau. The validation test results for developing an Argument-Driven Inquiry (ADI) based on PhET from each validator were 3.63%, 3.57%, and 3.53%, respectively. So that the average validator results reach 3.58% in the very valid category. Based on the results of the validity assessment, it can be concluded that the development of PhET-assisted Argument-Driven Inquiry (ADI)-based worksheets on substance pressure materials is included in the appropriate category to be used as teaching materials to train students’ argumentation skills in the learning process.